Polymorphism in Commercial Sources of Fusidic Acid: A Comparative Study of the In Vitro Release Characteristics of Forms I and III from a Marketed Pharmaceutical Cream - Jonathan Byrne; Robert Reinhardt; Trinidad Velasco-Torrijos (Journal of Analytical Methods in Chemistry)
A comparison of the polymorphic forms of 3 commercial sources of fusidic acid using FTIR and XRPD techniques has been performed in this study. It has been demonstrated that polymorphic Forms I and III are currently available on the commercial market. The influence of the observed polymorphism on the stability of the drug substance in bulk form has been investigated through stability and stress testing according to current ICH guidelines. Significant differences were detected between commercial sources with regard to the stability of the bulk substance under photolytic and humidity stress conditions. When properly packaged in an inert atmosphere, fusidic acid from all 3 manufacturers showed a comparable stability. The effects of the observed polymorphic differences on the intrinsic dissolution rate of the drug substance and its in vitro release from the marketed drug product Fusicutan® plus Betamethasone cream have been investigated. Results indicated that the release rate of the drug substance is similar for polymorphic Forms I and III, allowing both forms to be used during manufacture without affecting the safety or efficacy of the drug product.